Exploring the potential of probiotics in dentistry : a literature review = Explorando el potencial de los probióticos en odontología : una revisión de la literatura - Castro, Sofía
To describe the scientific literature on the uses and application of probiotics in dentistry. An electronic search was carried out without date restriction in the PubMed and Scopus databases. The articles were compiled, and their characteristics, objectives and methods were studied using the following keywords: "probiotics", "S. mutans", "oral health", "biofilm", among others. For the present literature review, 10 studies were chosen that investigate the probiotic action of certain strains such as Lactobaccillus and Bifidobacterium in periodontal and orthodontic treatments, among others. These studies proved their efficacy in different types of presentations such as tablets and yogurt, in different types of populations such as infants, young people and older adults. Finally, a large part of these studies determined biofilm reduction. Based on the research articles, strains such as Lactobaccillusand Bifidobacterium showed positive effects in the reduction of bacterial plaque such as S. mutans in short- and long-term periods in different populations. There is a large production of studies concerning the application of probiotics in dentistry. However, it is necessary to carry out studies with other types of bacteria and different vehicles to determine more precisely which species help to maintain oral health.